Pengaruh Trust terhadap Sekolah Efektif di Sekolah Dasar Kabupaten Deli Serdang - Amanah Surbakti (Mahesa Research Center, 2022)
This study aims to determine the effect of trust on effective schools. This research was conducted in elementary schools in Deli Serdang Regency in 2020. The population of this study were elementary school teachers in Deli Serdang as many as 334 people. The research method used in this study is quantitative research with an expost facto research design, namely the variables studied are not controlled and manipulated by the researcher, but the facts are disclosed based on the measurement of symptoms that have been owned or tested what will happen. The results found that trust has a very significant direct effect on effective schools of 0.47 so it can be concluded that Trust in the form of belief, positive thinking, opening up distance, providing opportunities for action and improving social relations with other people has an effect on program planning, implementation of work plans, supervision and evaluation, school leadership, management information system as a form of effective school. To create an effective school, trust from teachers and principals is needed.